Preoperative CA 19-9 Level as Additional Predictor of Pancreatic Head Adenocarcinoma Resectability - Pasihulizan, Pasihulizan; Putranto, Agi S. (The New Ropanasuri Journal of Surgery, 2021)
Introduction. Determining eligibility criteria for resection is the basis of pancreatic head adenocarcinoma treatment planning, yet the currently used CT scan only has 80% accuracy as its primary modality. This study aimed to investigate preoperative CA 19-9 level use to help predict resectability of pancreatic head adenocarcinoma. Method. Determining eligibility criteria for resection is the basis of pancreatic head adenocarcinoma treatment planning, yet the currently used CT scan only has 80% accuracy as its primary modality. This study aimed to investigate preoperative CA 19-9 level use to help predict resectability of pancreatic head adenocarcinoma. Results. There were 54 subjects enrolled in the study, with the Mean age of both unresectable and resectable subjects is 53.78±11.13 years. Twenty-nine were assigned as an unresectable group and 25 subjects as a resectable group. We found significant differences in CA 19-9 serum albumin levels and Karnofsky score between the resectable and unresectable groups. The cut-off point for CA 19-9 levels was 140.65 U/mL, with a sensitivity of 82.76% (64.23% -94.15%), specificity of 72.00% (50.61% -87.93 %), and AUC of 0.784. Conclusion. CA 19-9 was significantly associated with eligibility criteria for pancreatic head carcinoma resection. CA 19-9 has a good diagnostic value as an additional predictor for resectable pancreatic head carcinoma.